Basketball Sports Coaching Management - Siregar, Fajar Sidik; Andi Nur Abady (Journal Management of Sport, 2023)
The management of basketball sports coaching in Medan City in 2021 is still unknown, where the success of the Methodist club, one of which is determined by management and some administrators still do not carry out management functions or tasks in the Methodist club. Therefore, this study aims to determine how planning, organizing, implementing, and supervising basketball sports coaching management activities at Methodist in 2021. This research uses qualitative research with a descriptive approach, with the subjects of this research being the Chairperson, Coach, and athletes. Data collection using interview, observation, and documentation methods. Data analysis uses a method that is carried out continuously with data reduction, data presentation, and conclusion drawing. The results of this study: (1) Planning has not been programmed properly (2) Organizing is still not competent (3) the implementation of training is still often hampered due to lack of facilities and infrastructure (4) Supervision is still not perfect because it is only left to the coach. The conclusion from the results of the above research regarding the Methodist club is said to be not good. The author's suggestion to the Chairman of the Methodist club is to maintain good communication with all members so that they can achieve the targets that have been set.